A review of testate amoeba genus Cryptodifflugia Penard, 1890 (Phryganellina: Cryptodifflugiidae) with a key to species - Bobrov, Anatoly; Mazei, Yuri (Zootaxa, 2017)
The testate amoeba genus Cryptodifflugia is reviewed. Thirty-two taxa are described. Four taxa, namely Cryptodifflugia collum (Chardez, 1971), Cryptodifflugia minuta (Playfair, 1917), Cryptodifflugia patinata (Schönborn, 1965), Cryptodifflugia psammophila (Golemansky, 1970), appear as new combinations. A dichotomous identification key is provided.